Detection of drug‐responsive B lymphocytes and antidrug IgG in patients with β‐lactam hypersensitivity. Issue 6 (8th December 2016) - Amali, M. O.; Sullivan, A.; Jenkins, R. E.; Farrell, J.; Meng, X.; Faulkner, L.; Whitaker, P.; Peckham, D.; Park, B. K.; Naisbitt, D. J.
Abstract: Background: Delayed‐type β‐lactam hypersensitivity develops in subset of patients. The cellular immunological processes that underlie the drug‐specific response have been described; however, little is known about involvement of the humoral immune system. Thus, the aim of this study was to utilize piperacillin hypersensitivity as an exemplar to (i) develop cell culture methods for the detection of drug‐specific B‐cell responses, (ii) characterize drug‐specific IgG subtypes and (iii) assess reactivity of IgG antibodies against proteins modified to different levels with piperacillin haptens. Methods: IgG secretion and CD19 + CD27 + expression on B cells were measured using ELISPOT and flow cytometry, respectively. A piperacillin–BSA adduct was used as an antigen in ELISA antibody binding studies. Adducts generated using different ratios of drug to protein were used to determine the degree of conjugation required to detect IgG binding. Results: B cells from hypersensitive patients, but not controls, were stimulated to secrete IgG and increase CD27 expression when cultured with soluble piperacillin. A piperacillin–BSA adduct with cyclized and hydrolysed forms of the hapten bound to eight lysine residues was used to detect hapten‐specific IgG 1‐4 subclasses in patient plasma. Hapten inhibition and the use of structurally unrelated hapten–BSA adducts confirmed antigen specificity. Antibody binding was detected with antigens generated at piperacillin/BSA ratios of 10:1 and above, which corresponded to a minimum epitope density of 1 for antibody binding. Conclusion: These data show that antigen‐specific B lymphocytes and T lymphocytes are activated in piperacillin‐hypersensitive patients. Further work is needed to define the role different IgG subtypes play in regulating the iatrogenic disease.